Pengaruh Pemberian Silase Rumput Odot dengan Jerami Padi Sebagai Absorban Terhadap Konsentrasi Metabolit Darah pada Ternak Kambing - Maria Anaroja Naibesi; Marthen L. Mullik; Mariana Nenobais (Politeknik Kampar, 2024)
This study aims to determine the effect of giving odot grass silage with rice straw as absorbent on blood metabolite concentrations in goats. This study used a Latin square design with 4 treatments and 4 replications. The four treatments were JP0: silase consisting of 100% buckwheat, JP10: silase consisting of 90% mutton and 10% rice straw, JP20: silase consisting of 80% mutton and 20% rice straw, JP30: silase consisting of 70% odot and 30% rice straw. The data obtained were analyzed using Analysis of Variance (ANOVA) using SPSS 21. The parameters measured consisted of levels of erythrocytes, leukocytes, hemoglobin (Hb), packed cell volume (PCV). Absorbance had no significant effect (P>0,05) on the levels of erythrocytes, leukocytes, packed cell volume, and blood hemoglobin of kacang goats.